A model for determining the effect of the wind velocity on 100 m sprinting performance - Janjic, N.; Kapor, D.; Doder, D.; Petrovic, A.; Doder, R. (Journal of Human Kinetics, 2017)
This paper introduces an equation for determining instantaneous and final velocity of a sprinter in a 100 m run completed with a wind resistance ranging from 0.1 to 4.5 m/s. The validity of the equation was verified using the data of three world class sprinters: Carl Lewis, Maurice Green, and Usain Bolt. For the given constant wind velocity with the values + 0.9 and + 1.1 m/s, the wind contribution to the change of sprinter velocity was the same for the maximum as well as for the final velocity. This study assessed how the effect of the wind velocity influenced the change of sprinting velocity. The analysis led to the conclusion that the official limit of safely neglecting the wind influence could be chosen as 1 m/s instead of 2 m/s, if the velocity were presented using three, instead of two decimal digits. This implies that wind velocity should be rounded off to two decimal places instead of the present practice of one decimal place. In particular, the results indicated that the influence of wind on the change of sprinting velocity in the range of up to 2 m/s and was of order of magnitude of 10-3 m/s. This proves that the IAAF Competition Rules correctly neglect the influence of the wind with regard to such velocities. However, for the wind velocity over 2 m/s, the wind influence is of order 10-2 m/s and cannot be neglected.